Influence of hight - fat diets with different fatty-acid composition on rat periodontal condition - Markov, A. V. (Journal of Education, Health and Sport, 2017)
Aim: Determine the effect of high-fat diets (HFD) with different fatty acid composition on the condition of the gums of rats. Materials and Methods: 4 types of edible fats were used: sunflower oil ( main acid - linoleic), olive oil (main acid -oleic acid), palm oil ( main acid - palmitic acid) and butter (the main acids are palmitic acid, oleic acid, short- and medium- chain fatty acids). They were administered to rats in rations containing 15% of the above oils. Rats were fed for 41 days. The increase in live weight, the presence of hyperlipidemia, systemic inflammation, the presence of inflammation and the level of nonspecific immunity and antioxidant protection in the gums of rats were determined. Results: HFD containing high palmitic fats cause the development of obesity, hyperlipidemia, systemic inflammation, inflammation and dystrophic process in the gums, as well as a decrease in the level of nonspecific immunity and antioxidant protection. The smallest pathogenic effect has the consumption of olive oil. Conclusions: High-fat diet using high palmitic fats may be one of the main causes of periodontitis.